Teachers' beliefs on technological fusion in teaching ESL students - Kartar Singh, Kulwant Kaur; Yamat, Hamidah; Wahi, Wahiza (Scientific Research Publishing, 2018)
Studies on the effectiveness of technology have shown that it enhances students in language learning and helps gain their involvement. Nevertheless, there is still resistance among teachers in using technology in the language classrooms due to the rapid advancements of technology. The aim of the study reported in this article was therefore to gather testimonial insights on teachers' beliefs about technology and its fusion to illuminate how English as a second language (ESL) teaching and learning is eased and made meaningful in classrooms.